Hormonal control of the estrous cycle in cattle and sheep - Atuesta, Jorge; Gonella Diaza, Ángela (Spei Domus, 2011)
The goal of this review is conducting a detailed and updated literature description of hormonal mechanisms that regulate the estrous cycle. Indeed, we know that estrous cycle is the time period from one heat to the beginning of the next one. The endocrine events during the estrous cycle are regulated by hypothalamus (through GnRH secretion), the pituitary (lh and fsh secretion), the follicles (estrogens and inhibin secretion), the corpus luteum (progesterone and oxytocin), and uterus (responsible for production of prostaglandin F2α). Within proestrus, a quick decrease in plasma progesterone levels precedes the estrus caused by releasing prostaglandin F2 α from endometrium. Such reduction of progesterone concentrations allows the ovulatory follicle to grow and secrete estradiol; so plasma estradiol binding to specific receptors in the hypothalamus can set off the neural mechanism that triggers behavioral changes associated with the estrus onset. During estrus, or heat, the female is receptive to the male and allows mating. A peak in estradiol levels occurs shortly after the estrus onset and induces the lh pre-ovulatory discharge, which in turn induces the ovulation and the beginning of luteinization process of theca and granulose cells. A new corpus luteum is developed during metestrus with a subsequent increase in progesterone serum concentration. This corpus completes its maturation during diestrus. If a viable embryo in the uterus, it sends a signal for maternal recognition of pregnancy whose recognition prevents luteolisis process and, subsequently, the beginning of a new estrus cycle during pregnancy.